Improvement of Physical Performance Following a 6 Week Change-of-Direction Training Program in Elite Youth Soccer Players of Different Maturity Levels - Sariati, Dorsaf; Hammami, Raouf; Zouhal, Hassane; Clark, Cain C. T.; Nebigh, Ammar; Chtara, Mokhtar; Chortane, Sabri Gaied; Hackney, Anthony C.; Souissi, Nizar; Granacher, Urs; Ounis, Omar Ben (Frontiers in Physiology, 2021)
Background: Change-of-direction (CoD) is a necessary physical ability of a field sport and may vary in youth players according to their maturation status. Objectives: To compare the effectiveness of a 6-weeks CoD training intervention on dynamic balance (CS-YBT), horizontal jump (5JT), speed (10, and 30-m linear sprint times, CoD with (15m-CoD+B) and without (15m-CoD) the ball, in youth male soccer players at different levels of maturity (pre-and-post-peak height velocity [PHV]). Materials and Methods: Thirty young elite male youth soccer players aged 10-17 years from the Tunisian first division participated in this study. The players were divided into pre- (G1, n=15) and-post-PHV (G2, n=15) groups. Both groups completed a similar 6-weeks training program with two sessions per week of four CoD exercises. All players completed the following tests before, and after intervention: CS-YBT, 5 JT, 10-m, 30-m, 15m-CoD, and 15m-CoD+B, and data were analyzed using ANCOVA. Results: All 30 players completed the study according to the study design and methodology. Adherence rate was 100% across all groups and no training or test-related injuries were reported. Pre-PHV and post-PHV groups showed significant amelioration post-intervention for all dependent variables (after-test > before-test; p<0.01, d = 0.09–1.51). ANOVA revealed a significant group x time interaction only for CS-YBT (F=4.45; p<0.04; 2=0.14), 5JT (F=6.39; p<0.02; 2= 0.18) and 15m-CoD (F=7.88; p<0.01; 2=0.22). CS-YBT, 5JT and 15m-CoD improved significantly in the post-PHV group (+4.56%, effect size = 1.51, +4.51%, effect size = 1.05 and -3.08%, effect size = 0.51, respectively), more than the pre-PHV group (+2.77%, effect size = 0.85, +2.91%, effect size = 0.54 and -1.56%, effect size = 0.20, respectively). Conclusion: The CoD training program improved balance, horizontal jump, and CoD without the ball in male preadolescent and adolescent soccer players, and this improvement was greater in the post-PHV players. The maturity status of the athletes should be considered when programming CoD training for soccer players.